2014
DOI: 10.1186/1472-6963-14-111
|View full text |Cite
|
Sign up to set email alerts
|

Urban settings do not ensure access to services: findings from the immunisation programme in Kampala Uganda

Abstract: BackgroundPrevious studies on vaccination coverage in developing countries focus on individual- and community-level barriers to routine vaccination mostly in rural settings. This paper examines health system barriers to childhood immunisation in urban Kampala Uganda.MethodsMixed methods were employed with a survey among child caretakers, 9 focus group discussions (FGDs), and 9 key informant interviews (KIIs). Survey data underwent descriptive statistical analysis. Latent content analysis was used for qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 34 publications
5
41
1
3
Order By: Relevance
“…Similar studies assessing the quality of service in public clinics in South Africa showed that the clinics were easily accessible and services were of acceptable quality [38], but the time spent by patients at the clinic to complete the services was very long [38, 39]. These findings suggest that public health services in many resource-constrained LMICs are characterised by long waiting periods [4042], which could be a consequence of operational challenges such as performance of multiple tasks and work overload of health workers [18]. In addition to staff shortage which was reported by operational managers and patients in the qualitative component [43] of the broader mixed methods study, patients who missed previous clinic appointments were being made to wait in the queues during subsequent visits until nurses had attended to patients who were on the appointment list for that day [43].…”
Section: Discussionmentioning
confidence: 88%
“…Similar studies assessing the quality of service in public clinics in South Africa showed that the clinics were easily accessible and services were of acceptable quality [38], but the time spent by patients at the clinic to complete the services was very long [38, 39]. These findings suggest that public health services in many resource-constrained LMICs are characterised by long waiting periods [4042], which could be a consequence of operational challenges such as performance of multiple tasks and work overload of health workers [18]. In addition to staff shortage which was reported by operational managers and patients in the qualitative component [43] of the broader mixed methods study, patients who missed previous clinic appointments were being made to wait in the queues during subsequent visits until nurses had attended to patients who were on the appointment list for that day [43].…”
Section: Discussionmentioning
confidence: 88%
“…Barriers to access have been primarily researched for rural settings, but are equally relevant for those hard to reach in urban settings. 73 Lack of financial protection is a significant financial barrier to access and can lead to catastrophic health expenditures. Available data for eight sub-Saharan countries (Ghana, Kenya, Malawi, Niger, Senegal, Uganda, Tanzania, and Zambia) suggest that more than a quarter of the population may be further pushed into poverty by OOP payments on health services.…”
Section: Health Systems In Sub-saharan Africamentioning
confidence: 99%
“…These include caregiver literacy and employment [7–11], geographic location [7, 8, 12, 13], maternal utilization of other health services and place of childbirth [7, 14], safety concerns, and misconceptions about vaccines [15, 16]. Lack of awareness in the form of poor understanding of benefits, dosing and schedules [10, 12, 14, 17, 18], is also among the commonly reported reasons for defaulting from the program.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies also identified household income, child illness [19, 20], poor male partner involvement [15], and large family size [16] to be associated with defaulting. Incomplete immunization is also commonly linked to weaknesses in the health systems, such as the lack of vaccines during vaccination sessions [17] and poor geographic access and long distance from the sites [7, 8, 12, 15, 21], including in urban settings [13]. Poor service arrangements with long waiting time [13, 15], inconvenient schedules [16], unwelcoming health care environment [16, 19], and not holding sessions as planned [22] were also mentioned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation